Prevention of malaria in pregnancy through health education intervention programs on insecticide-treated nets use: a systematic review - Onyinyechi, Opara Monica; Ismail, Suriani; Nashriq Mohd Nazan, Ahmad Iqmer (BioMed Central, 2024)
Malaria is a widespread and prevalent disease that affects human population globally, particularly in tropical countries. Malaria is a major health issue in sub-Saharan Africa and it contributes to morbidity and mortality among individuals in Africa. Pregnant women have been also reported as high risk of people been infected with malaria. This review attempted to evaluate the various methods used for health education programs and the effectiveness of the programs in improving ITNs among pregnant women. Methods The search involved various databases; EBCOHOST, MEDLINE, CINAHL, Cochrane library, ScienceDirect, PubMed, SAGE, Sringer link, Web of Science and Wiley Online Library. It was limited to full text research articles that report intervention studies, written in English Language, published between 2003 to 2022. The key words were “malaria”, “malaria prevention”, “health education”, “insecticide-treated nets”, “utilization”, “pregnant women”. Results A total of eleven articles met the inclusion criteria and included in the review. Six studies reported randomized controlled trials (RCTs) while five reported non-randomized controlled trials (NRCT). Conclusions There are evidences from the results which showed that health education programs were improved among pregnant women due to the use of ITNs and LLINS utilization. Furthermore, additional interventions directed at significant others need to be implemented, considering their important role in determining pregnant women’s use of ITNs.